Evolution of Weyl orbit and quantum Hall effect in Dirac semimetal Cd3As2 - Cheng Zhang (Nature Portfolio, 2017)
A new type of cyclotron orbit combining surface Fermi arcs and bulk states in topological semimetals has recently been proposed as Weyl orbit. Here, Zhang et al. report the evolution of Shubnikov-de Haas oscillations in Dirac semimetal Cd3As2 nanoplates along with a quantum Hall state possibly arising from such Weyl orbit.